Evidence-Based Guidelines for the Treatment of Helicobacter pylori Infection in Korea 2020 - Jung, Hye-Kyung; Kang, Seung Joo; Lee, Yong Chan; Yang, Hyo-Joon; Park, Seon-Young; Shin, Cheol Min; Kim, Sung Eun; Lim, Hyun Chul; Kim, Jie-Hyun; Nam, Su Youn; Shin, Woon Geon; Park, Jae Myung; et al. (Gut and liver, 2021)
infection is one of the most common infectious diseases worldwide. Although the prevalence of is gradually decreasing, approximately half of the world's population still becomes infected with this disease. is responsible for substantial gastrointestinal morbidity worldwide, with a high disease burden. It is the most common cause of gastric and duodenal ulcers and gastric cancer. Since the revision of the clinical practice guidelines in 2013 in Korea, the eradication rate of has gradually decreased with the use of a clarithromycin-based triple therapy for 7 days. According to a nationwide randomized controlled study conducted by the Korean College of and Upper Gastrointestinal Research released in 2018, the intention-to-treat eradication rate was only 63.9%, which was mostly due to increased antimicrobial resistance, especially from clarithromycin. The clinical practice guidelines for the treatment of were updated according to evidence-based medicine from a meta-analysis conducted on a target group receiving the latest level of eradication therapy. The draft recommendations developed based on the meta-analysis were finalized after an expert consensus on three recommendations regarding the indication for treatment and eight recommendations for the treatment itself. These guidelines were designed to provide clinical evidence for the treatment (including primary care treatment) of infection to patients, nurses, medical school students, policymakers, and clinicians. These may differ from current medical insurance standards and will be revised if more evidence emerges in the future.